Regulatory mechanisms of fospropofol on cerebral blood flow and metabolism and its clinical applications: Recent advances - Luying Huang; Hui Yang (Saudi Journal of Anaesthesia, 2025)
Fospropofol is a water-soluble prodrug of propofol that has gained increasing attention in the field of anesthesia due to its gentle modulation of cerebral blood flow and metabolism. This review summarizes the pharmacological mechanisms by which fospropofol regulates cerebral hemodynamics, including direct effects on vascular smooth muscle and indirect modulation via suppression of neural metabolic activity. The article also discusses its ability to reduce cerebral metabolic rate, inhibit neuronal excitability, and modulate energy balance, all of which contribute to its potential neuroprotective properties, particularly in ischemia-reperfusion injury. Preclinical and clinical studies suggest that fospropofol exerts antioxidant and anti-inflammatory effects that may further support neural preservation. Clinically, fospropofol has shown value in various scenarios requiring precise neuromanagement, including neurosurgery, anesthesia in elderly patients, intensive care sedation, and perioperative neuroprotection. Despite promising results, further high-quality, large-scale studies are needed to clarify its neuroprotective efficacy across diverse patient populations and surgical contexts. With its favorable pharmacokinetics, controllable depth of sedation, and multitargeted neural effects, fospropofol is poised to become an important tool in individualized neuroanesthesia and brain-protective strategies.